2018
DOI: 10.3390/polym10030292
|View full text |Cite
|
Sign up to set email alerts
|

Extraction Optimization, Purification, Antioxidant Activity, and Preliminary Structural Characterization of Crude Polysaccharide from an Arctic Chlorella sp.

Abstract: Abstract:The arctic strain of Chlorella sp. (Chlorella-Arc) exists in the coldest and driest arctic ecosystems, and it is a new resource of active polysaccharides. The extraction of crude polysaccharide from Chlorella-Arc was optimized using the response surface methodology. A crude polysaccharide yield of approximately 9.62 ± 0.11% dry weight was obtained under these optimized conditions. Three fractions (P-I, P-II, and P-III) were present after purification by 2-diethylaminoethanol Sepharose Fast Flow and Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 57 publications
(103 reference statements)
3
29
0
Order By: Relevance
“…The hot water extraction (HWE) was performed according to a previously reported method with some modifications [31]. Briefly, the snow chrysanthemum powders (1.0 g) were firstly refluxed with 10 mL of 80% ( v / v ) ethanol at 80 °C for 2 h to remove most of the small molecules.…”
Section: Methodsmentioning
confidence: 99%
“…The hot water extraction (HWE) was performed according to a previously reported method with some modifications [31]. Briefly, the snow chrysanthemum powders (1.0 g) were firstly refluxed with 10 mL of 80% ( v / v ) ethanol at 80 °C for 2 h to remove most of the small molecules.…”
Section: Methodsmentioning
confidence: 99%
“…Microalgal polysaccharides also showed potent activity toward different free radical scavenging [126][127][128]. Sun et al [54] obtained two polysaccharides (P-0 and S-0) from algae Pavlova viridis and Sarcinochrysis marina Geitler, and found that the degraded polysaccharides (P-2 and S-3) showed stronger antioxidant activity than the undegraded polysaccharides (P-0 and S-0) ( Table 1).…”
Section: Microalgal Polysaccharidesmentioning
confidence: 99%
“…The reagent used to dissolve the alginate oligosaccharides was set as the blank, and Vc was used as the positive control. The percentage of scavenged ABTS radical was calculated with the following equation:where A is the absorbance of the blank at 734 nm, and B is the final absorbance of each sample at 734 nm.The scavenging activity of hydroxyl radical was measured in accordance with previously reported methods(Song et al, 2018) with slight modifications. In brief, FeSO 4 (0.1 ml, 9.0 mM), deionized water (0.6 ml), and ethanol salicylate (0.1 ml, 9.0 mM) were mixed with a polysaccharide solution (0.2 ml).…”
mentioning
confidence: 99%